First in vivo test of a biodegradable polymeric stent for the Eustachian tube in sheep - Winkelmann, Stina; Lebahn, Kerstin; Ezzat, Malena; Schmitt, Katharina; Napp, Alexandra; Oppel, Niels; Pohl, Friederike; Kampmann, Andreas; Grabow, Niels; Lenarz, Thomas; Paasche, Gerrit (Frontiers in Audiology and Otology, 2024)
Introduction Eustachian tube dysfunction can cause inadequate ventilation of the middle ear and is therefore one of the main reasons for the development of chronic middle ear infections. This can significantly impact the quality of life. There is a variety of treatment options, but in most cases long-term success is limited. For this reason, stenting the Eustachian tube (ET) may be a safe and effective alternative. Biodegradable stents have been developed that support the impaired ET function until natural ventilation of the middle ear via the ET is restored, and dissolve after their function has been fulfilled. Objective The purpose of the current study was to investigate feasibility of implantation and degradation kinetics of biodegradable polymer stents in the ET. Study design The study was set up as an orientation study. Methods Biodegradable stents (diameter: 3.5 mm; length: 15 mm) were made from Poly-L-lactic acid (PLLA) in a dip-coating process and subsequent laser cutting and were crimped on a balloon catheter. Stent implantation into the ET was performed unilaterally in nine healthy female blackface sheep under endoscopic control with a dedicated insertion tool and an inflation pressure of 10 bar for 2 min. Ventilation of the middle ear was controlled by tympanometry weekly throughout the observation period of 3, 6, or 12 months (three animals each). After the final examination, cone beam computed tomography scans and histological examinations of the ETs were performed. Results All stents could be inserted as planned. Pharyngeal orifices of all sheep were closed at half-time and final follow-up inspections. After 3 months, all stents were functional, but already showed first fragment formation. Six months after insertion, the stents had largely collapsed but still held open a residual lumen and after 12 months, the ETs were completely collapsed close to their natural shape. Fragments of various sizes were found distributed in the tissue beneath an epithelialized ET. Conclusion The polymeric ET stent can be reliably positioned without generating a patulous ET. It seems to support ET function for about 3 months before functionality is lost.